An algebra problem by Wildan Bagus Wicaksono

Algebra Level 3

f ( n ) = 4 n + 4 n 2 1 2 n + 1 + 2 n 1 f(n)=\frac { 4n+\sqrt { 4{ n }^{ 2 }-1 } }{ \sqrt { 2n+1 } +\sqrt { 2n-1 } }

Function f : N R f : \mathbb {N \to R} is defined as above. Determine f ( 13 ) + f ( 14 ) + f ( 15 ) + . . . + f ( 112 ) f(13)+f(14)+f(15)+...+f(112) .


The answer is 1625.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

f ( n ) = 4 n + 4 n 2 1 2 n + 1 + 2 n 1 f ( n ) = 4 n + 4 n 2 1 2 n + 1 + 2 n 1 2 n + 1 2 n 1 2 n + 1 2 n 1 f ( n ) = ( 4 n + 4 n 2 1 ) ( 2 n + 1 2 n 1 ) ( 2 n + 1 ) ( 2 n 1 ) f ( n ) = 1 2 { [ ( 2 n + 1 ) + ( 2 n 1 ) + 2 n + 1 2 n 1 ] ( 2 n + 1 2 n 1 ) } f ( n ) = 1 2 { ( 2 n + 1 ) 2 n + 1 ( 2 n 1 ) 2 n 1 } f(n)=\frac { 4n+\sqrt { 4{ n }^{ 2 }-1 } }{ \sqrt { 2n+1 } +\sqrt { 2n-1 } } \\ f(n)=\frac { 4n+\sqrt { 4{ n }^{ 2 }-1 } }{ \sqrt { 2n+1 } +\sqrt { 2n-1 } } \cdot \frac { \sqrt { 2n+1 } -\sqrt { 2n-1 } }{ \sqrt { 2n+1 } -\sqrt { 2n-1 } } \\ f(n)=\frac { \left( 4n+\sqrt { 4{ n }^{ 2 }-1 } \right) \left( \sqrt { 2n+1 } -\sqrt { 2n-1 } \right) }{ (2n+1)-(2n-1) } \\ f(n)=\frac { 1 }{ 2 } \left\{ \left[ (2n+1)+(2n-1)+\sqrt { 2n+1 } \cdot \sqrt { 2n-1 } \right] \left( \sqrt { 2n+1 } -\sqrt { 2n-1 } \right) \right\} \\ f(n)=\frac { 1 }{ 2 } \left\{ (2n+1)\sqrt { 2n+1 } -(2n-1)\sqrt { 2n-1 } \right\}

f ( 13 ) = 1 2 { 27 27 25 25 } f ( 14 ) = 1 2 { 29 29 27 27 } f ( 15 ) = 1 2 { 31 31 29 29 } f ( 112 ) = 1 2 { 225 225 223 223 } f(13)=\frac { 1 }{ 2 } \left\{ 27\sqrt { 27 } -25\sqrt { 25 } \right\} \\ f(14)=\frac { 1 }{ 2 } \left\{ 29\sqrt { 29 } -27\sqrt { 27 } \right\} \\ f(15)=\frac { 1 }{ 2 } \left\{ 31\sqrt { 31 } -29\sqrt { 29 } \right\} \\ \dots \\ f(112)=\frac { 1 }{ 2 } \left\{ 225\sqrt { 225 } -223\sqrt { 223 } \right\}

f ( 13 ) + f ( 14 ) + f ( 15 ) + . . . + f ( 112 ) = 1 2 { 225 225 25 25 } f ( 13 ) + f ( 14 ) + f ( 15 ) + . . . + f ( 112 ) = 1 2 { 225 15 25 5 } f ( 13 ) + f ( 14 ) + f ( 15 ) + . . . + f ( 112 ) = 1 2 ( 3375 125 ) f ( 13 ) + f ( 14 ) + f ( 15 ) + . . . + f ( 112 ) = 1625 f(13)+f(14)+f(15)+...+f(112)=\frac { 1 }{ 2 } \left\{ 225\sqrt { 225 } -25\sqrt { 25 } \right\} \\ f(13)+f(14)+f(15)+...+f(112)=\frac { 1 }{ 2 } \left\{ 225\cdot 15-25\cdot 5 \right\} \\ f(13)+f(14)+f(15)+...+f(112)=\frac { 1 }{ 2 } (3375-125)\\ f(13)+f(14)+f(15)+...+f(112)=1625

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...